Metaphor Use in ABBA Song Lyrics - Nuraini, Risqi; Pakaya, Usman; Bay, Indri Wirahmi (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2026)
This study analyzes conceptual metaphors in two ABBA songs, namely “Slipping Through My Fingers” and “The Winner Takes It All.” The analysis applies Lakoff and Johnson’s (1980) theory, which classifies metaphors into three types: structural, ontological, and orientational metaphors. The data consist of 17 metaphorical expressions collected through documentation techniques and analyzed using a descriptive qualitative method. The results show that “Slipping Through My Fingers” is dominated by ontological metaphors that conceptualize time, memory, and emotions as physical entities that can be held, stored, or lost. Meanwhile, “The Winner Takes It All” is dominated by structural metaphors that represent romantic relationships as a competitive game involving winning, losing, and rules. These findings demonstrate that metaphors in both songs strengthen emotional expression and transform abstract experiences into concrete and perceptible imagery